2010
DOI: 10.1089/jwh.2009.1670
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Recommended Gynecologic Care in an Urban United States HIV Clinic

Abstract: Gynecologic healthcare is underused among HIV-infected women. We found that depressive symptoms, substance use, fear of the gynecologic examination, and simply forgetting about the appointment may be barriers to gynecologic care. Interventions targeting these barriers may improve use of gynecologic care among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
6
25
0
Order By: Relevance
“…If both tests are normal, screening can be reduced to an annual schedule (Kaplan et al, 2009). Despite guidelines aimed to decrease the heavy burden of cervical cancer among HIV-infected women, Papanicolaou (Pap) screening is still underutilized by this population of women (Baranoski, Horsburgh, Cupples, Aschengrau, & Stier, 2011; Fletcher et al, 2013; Keiser et al, 2006; Logan, Khambaty, D'Souza, & Menezes, 2010; Oster, Sullivan, & Blair, 2009; Tello et al, 2010). However, a consensus is lacking on the most important barriers to cervical cancer screening utilization among HIV-infected women.…”
Section: Introductionmentioning
confidence: 99%
“…If both tests are normal, screening can be reduced to an annual schedule (Kaplan et al, 2009). Despite guidelines aimed to decrease the heavy burden of cervical cancer among HIV-infected women, Papanicolaou (Pap) screening is still underutilized by this population of women (Baranoski, Horsburgh, Cupples, Aschengrau, & Stier, 2011; Fletcher et al, 2013; Keiser et al, 2006; Logan, Khambaty, D'Souza, & Menezes, 2010; Oster, Sullivan, & Blair, 2009; Tello et al, 2010). However, a consensus is lacking on the most important barriers to cervical cancer screening utilization among HIV-infected women.…”
Section: Introductionmentioning
confidence: 99%
“…However, the biggest barrier to appointment attendance in this study was forgetting about the appointment; 61% of those who missed appointments reported ''forgetting'' as the reason. 1 Because forgetting plays such a large role in adherence to medical care, novel strategies are needed to address this issue. Americans are increasingly using cellular phones in their daily life, and many use these phones to send text messages.…”
mentioning
confidence: 99%
“…Other major HPVassociated cancers in HIV-infected individuals, including cervical cancer, suffer from poor follow-up screening rates as well. 48,49 One study of barriers to recommended cervical cancer screening in HIV-infected women found that depressive symptoms, substance use, fear of gynecologic examination and simply forgetting the appointment may be barriers to cervical cancer screening in HIV-infected women. 51 Some of those barriers may be applicable to barriers associated with poor anoscopy follow-up.…”
mentioning
confidence: 99%